Closing Editorial for Applications of Fractional-Order Systems in Automatic Control - German A. Munoz-Hernandez; Jose Fermi Guerrero-Castellanos (Fractal and Fractional)
Fractional-order systems have been applied in very diverse areas of science and engineering [...]